Optimization of extraction for phenolic compound from the peel of limau kasturi (Citrus Macrocarpa) - Rubiatul Adawiah Sa'adi (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
This work reports a study on parameters optimization of essential oil extraction from the Rutaceae family, which is a Citrus species, named Citrus macrocarpa using soxhlet extraction. The important of TPC is because of the availability of phenolic compounds in limaukasturi peels as an antioxidant source which contributed to the protection of DNA from cancer-causing damage. The optimum conditions of the process parameters were determined by employing response surface methodology (RSM) coupled with central composite design (CCD). It was predicted that the optimum extraction process parameters within the experimental ranges would be the extraction time of 5 h 30 min, particle size 0.250 mm and methanol concentration of 60 %. Under this condition, the highest total phenolic content which about 9.51 mg GAE/g DW was obtained. Results showed that the data were adequately fitted into the second-order polynomial model.